Preparation method of low-temperature coating catalyst
By pretreating the waste catalyst and mixing it with other materials, forming a slurry, coating it on ceramics, and producing a low-temperature coated catalyst, the problem of existing catalysts being easily poisoned and inactivated in a low-temperature environment is solved, and cost reduction, activity improvement and environmentally friendly effects are achieved.
Patent Information
- Application Number
- CN202411944036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing low-temperature coating catalysts are easily blocked by soot and alkali metals in high dust and high sulfur environments, resulting in poisoning and inactivation, and have high preparation costs and fewer applications.
Regenerated titanium dioxide is prepared by pretreating the waste catalyst, including sieving, grinding, calcining and cleaning, and mixed with other materials such as ammonium metavanadate, ammonium metatungstate, oxalic acid, acrylamide, methylenebisacrylamide and starch, to form a slurry, coated on ceramics, and made a low-temperature coating catalyst by gel curing and calcining.
It reduces the preparation cost and time of the catalyst, improves the activity and weather resistance of the catalyst, extends the service life, and effectively removes impurities and metal ions in the catalyst, reducing environmental pollution.
Smart Images

Figure CN119793440A_ABST
Abstract
Description
[0001] The invention relates to the technical field of low-temperature coated catalysts, in particular to a method for preparing a low-temperature coated catalyst. Background Art
[0002] Nitrogen oxides (NO x ) is one of the important causes of photochemical smog, greenhouse effect, ozone layer depletion, acid rain and PM2.5. my country's nitrogen oxide emissions mainly come from the combustion of fossil fuels. Among them, 70% comes from the direct combustion of coal, and the coal consumption of thermal power plants accounts for 70% of the country's coal consumption, becoming one of the main sources of nitrogen oxide pollutants. Ammonia selective catalytic reduction denitrification technology is the most widely used and effective nitrogen oxide emission reduction technology.
[0003] At present, commercial vanadium-based catalysts show excellent denitrification performance in the medium and high temperature range (300-500°C), but in places such as coal-fired plants, cement plants, and waste incineration plants, the catalysts are in a high-dust and high-sulfur environment, which makes them easily blocked by smoke dust, and poisoned and inactivated by alkali metals occupying acid sites and SO2 sulfation. After desulfurization and dust removal of flue gas, the flue gas becomes relatively clean, which can effectively solve the above problems, but the flue gas temperature drops sharply after pretreatment (<200°C). At low temperatures, a large amount of water vapor and a small amount of SO2 retained in the flue gas not only compete with the reaction gas for adsorption, but also easily generate ammonium bisulfate (ABS) to poison and inactivate the catalyst. Therefore, the cost of low-temperature coated catalysts is generally high, and one-piece catalysts are the main ones, and the application of low-temperature coated catalysts is relatively small. Based on the above, a preparation method of a low-temperature coated catalyst was studied. Summary of the invention
[0004] To achieve the above object, the present invention provides a method for preparing a low-temperature coated catalyst and a preparation method thereof.
[0005] The present invention provides a method for preparing a low-temperature coated catalyst, comprising the following steps: a pretreatment step: grinding the waste catalyst after screening and deashing to obtain a grind, mixing it with soda ash and roasting it to obtain a mixture, washing it for solid-liquid separation, washing it with a dilute sulfuric acid solution, ball milling it to obtain a pre-slurry, mixing the pre-slurry with titanic acid and spray-drying it to form regenerated titanium dioxide.
[0006] Furthermore, the spent catalyst contains TiO2, V2O5 and WO3.
[0007] Furthermore, in the pretreatment step, the waste catalyst is screened and deashed and then ground to a material particle size of 30-50 mesh; the mass ratio of the ground material to soda ash is 1:0.2, and the roasting temperature is 750°C; it is washed with three times the mass of pure water; the pH value is adjusted to 3, and the solid-liquid separation is performed by standing for 50 minutes; it is washed with a 1% dilute sulfuric acid solution to a pH value of 3; the pre-slurry particle size is 800-1000 mesh; the pre-slurry is mixed with titanic acid in a mass ratio of 1:0.1 and spray-dried.
[0008] Furthermore, the method also includes the step of preparing slurry B: adding regenerated titanium dioxide to a mixed solution containing ammonium metavanadate, ammonium metatungstate and oxalic acid, stirring in a water bath to evaporate to dryness, and calcining to obtain catalyst A; mixing silicon dioxide dispersion, hydrated aluminum oxide dispersion, acrylamide, methylenebisacrylamide and starch to obtain a premixed solution; adding silicon carbide powder and graphite powder; and adding a 10% aqueous solution of tetramethylammonium hydroxide; adding catalyst A and ball milling for 2 hours to prepare slurry B.
[0009] Further, after stirring, the mixture was evaporated to dryness in a water bath at 80° C.; and calcined at 500° C. for 4 hours to obtain Catalyst A.
[0010] Furthermore, the method also includes the steps of preparing ceramics: mixing kaolin, talc and alumina, adding methyl metal saponification liquid, methyl cellulose and polyether polyol, kneading and mixing the clay, aging the clay once, refining and aging the clay twice, sieving the clay to obtain a clay material, putting the clay material into an extruder to obtain a ceramic green body, and calcining the clay to obtain a ceramic.
[0011] Furthermore, the kaolin, talc and alumina are mixed in a ratio of kaolin: talc: alumina = 4:3:3 according to weight; the mass percentage concentration of the methyl metal saponification solution is 0.25%, the mass percentage concentration of methyl cellulose is 1%, and the mass percentage concentration of the polyether polyol is 0.5%; the first aging is a room temperature reaction for 12 hours; the second aging is a room temperature reaction for 16 hours; sieving through a 250 mesh sieve 3 times; and calcining at a high temperature of 1350°C to obtain ceramics.
[0012] Furthermore, the method also includes the step of preparing a low-temperature coated catalyst: immersing the ceramic in slurry B, adding an 8% aqueous solution of ammonium persulfate and tetramethylethylenediamine, gelling and solidifying at 60° C., and heat-insulating, drying and calcining to obtain a low-temperature coated catalyst.
[0013] Further, the ceramic was immersed in slurry B for 5 minutes; 0.6% of the mass of slurry B was added with 8% aqueous solution of ammonium persulfate and 0.6% of tetramethylethylenediamine, and placed in an incubator at 60°C for gel curing for 5 hours, dried at 120°C for 6 hours, and calcined at 500°C to obtain a low-temperature coated catalyst.
[0014] Furthermore, the pretreatment step also includes washing the calcined mixture with three times the mass of pure water to obtain a pre-chelate, adding 8 parts of γ-polyglutamic acid to 120 parts of deionized water by mass, stirring evenly and drying at 120°C, crushing after drying, adding 10 parts of EDTMPA at 40°C to obtain a glutamate chelate, mixing the pre-chelate with the glutamate chelate in a mass ratio of 1 to 0.2, and separating the solid from the liquid.
[0015] The present invention provides a method for preparing a low-temperature coated catalyst, and a method and application thereof, which have the following beneficial effects:
[0016] 1. Compared with the one-piece catalyst, the coated catalyst has advantages in preparation cost and time. Some waste catalysts cannot be recycled due to insufficient matrix strength, but the TiO2, V2O5 and WO3 components in the waste catalysts still have utilization value. The waste catalysts, oxalic acid, ammonium metavanadate and ammonium metatungstate are used as raw materials to prepare catalyst A; then the prepared catalyst A is mixed with a binder (silicon dioxide dispersion, hydrated aluminum oxide dispersion, etc.) to form a slurry; then kaolin, talc and aluminum oxide are used as raw materials to prepare ceramics; finally, the slurry is coated on the ceramics to obtain a catalyst;
[0017] 2. The reaction principle of glutamic acid chelating agent is based on the formation of stable cyclic chelates by multiple coordinating atoms (such as nitrogen, oxygen, etc.) in its molecular structure and metal ions (such as K, Fe, Na, As, etc.). This cyclic structure enables the chelating agent to tightly "grasp" metal ions to form stable compounds that are difficult to dissolve or insoluble in water, and can selectively combine with impurity metal ions in the waste SCR catalyst to form stable chelates, thereby effectively removing these impurities. Due to the selectivity of the chelating agent for metal ions, it usually does not react with valuable components such as TiO2, V2O5 and WO3, thereby protecting the stability and integrity of these components. Through chelation, harmful metal ions in the waste SCR catalyst can be converted into stable compounds, reducing the pollution of these metal ions to the environment;
[0018] 3. Silica dispersion has high stability and transparency, and can form a uniform coating. The silica dispersion particles have huge specific surface area and activity, which can improve the adhesion of the coating. The hydrated aluminum oxide dispersion has nanometer-scale particle size and high specific surface area, which can significantly improve the dispersibility and stability of the coating. The adhesion of the hydrated aluminum oxide dispersion helps to enhance the adhesion between the coating and the substrate. The hydrated aluminum oxide dispersion can also reflect ultraviolet rays to prevent ultraviolet rays from damaging the catalyst, thereby enhancing the weather resistance of the catalyst. Starch is a natural polymer compound with good adhesion and film-forming properties. Adding starch to the slurry can significantly increase the viscosity of the slurry, thereby improving the coating performance, and can also improve the mechanical properties and chemical resistance of the catalyst. Acrylamide is a high molecular polymer with good water absorption and water retention. It can significantly increase the viscosity of the slurry and improve the fluidity of the slurry, making it easier to coat the slurry on the substrate. Acrylamide can also provide reinforcement and protection, improving the durability and chemical corrosion resistance of the catalyst.
[0019] 4. Gel curing using 8% aqueous solution of ammonium persulfate (ASP) as an initiator and 0.6% tetramethylethylenediamine (TEMED) as a catalyst is beneficial to the uniform distribution of the active components of the catalyst and the optimization of the pore structure, making the catalyst have a higher catalytic efficiency and a longer service life. The catalyst after gel curing has better thermal stability and mechanical strength, can maintain stable catalytic performance under a wider range of environmental conditions, and improves the applicability and reliability of the catalyst. Since the gel curing process can significantly shorten the preparation time, it can also reduce energy consumption to a certain extent and improve the environmental friendliness of the preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is the activity diagram of catalyst A;
[0021] Figure 2 This is the activity diagram of catalyst A at 210℃ under 100ppm SO2 for 100h;
[0022] Figure 3 This is the test diagram of catalyst A's denitrification efficiency;
[0023] Figure 4 This is a process flow chart of Example 2 of the present invention. DETAILED DESCRIPTION
[0024] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0025] Unless otherwise specified, the examples and comparative examples are parallel tests with the same components, component contents, preparation steps and preparation parameters. The experimental methods in the following examples are conventional methods unless otherwise specified. The experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.
[0026] Unless otherwise stated, all reagents were used as received without further purification.
[0027] In the preparation examples and embodiments of the present invention, the “parts” are parts by mass unless otherwise specified, and the concentration percentages are mass concentrations unless otherwise specified.
[0028] Example 1
[0029] This embodiment provides a low-temperature coated catalyst, and the preparation method thereof specifically comprises the following steps:
[0030] (1) Pretreatment: The waste catalyst (TiO2, V2O5 and WO3 components in the waste catalyst still have utilization value) is sieved and deashed, and then ground to a material particle size of 40 mesh to obtain a powder, and then the powder is mixed with soda ash at a mass ratio of 1 to 0.2. The mixed material is roasted at a roasting temperature of 750°C, and the roasted mixture is washed with three times the mass of water to obtain a pre-chelate, and 8 parts of γ-polyglutamic acid are added to 120 parts of deionized water by mass, stirred evenly, and then dried at 120°C. After drying, the mixture is crushed and 10 parts of EDTMPA (ethylenediaminetetramethylphosphonic acid) are added at 40°C to obtain a glutamic acid chelating agent, and the pre-chelate and the glutamic acid chelating agent are mixed and stirred at a mass ratio of 1 to 0.2.
[0031] Sulfuric acid was added to make the solution pH value 3, and the solution was allowed to stand for 50 minutes to perform solid-liquid separation to obtain slag, which was washed with a 1% dilute sulfuric acid solution. When the pH of the washing solution was 3, the acid washing was stopped, and the slag was washed with pure water of the same mass as the slag. The slag was then ball-milled to prepare a pre-slurry with a pre-slurry particle size of 1000 mesh. The pre-slurry was mixed with titanic acid in a mass ratio of 1 to 0.1, and the mixed material was spray-dried at 350° C. to form regenerated titanium dioxide after drying.
[0032] (2) Preparation of slurry B: Add regenerated titanium dioxide to a solution of ammonium metavanadate, ammonium metatungstate and oxalic acid, stir evenly, evaporate to dryness in a water bath at 80°C, and calcine at 500°C for 4 hours to obtain catalyst A. 20 parts by mass of a 20% silicon dioxide dispersion, 10 parts by mass of a 10% aluminum oxide hydrate dispersion, 25 parts by mass of acrylamide, 4.2 parts by mass of methylenebisacrylamide and 5 parts by mass of starch are mixed to obtain a premixed solution, silicon carbide powder with a particle size of 20 μm and graphite powder with a particle size of 5 μm are added to the premixed solution at a mass ratio of 15:1, and a 10% tetramethylammonium hydroxide (TMAH) aqueous solution with a powder mass fraction of 1.5% is added as a dispersant, SiC and graphite powder account for 48% of the total volume, 30 parts by mass of catalyst A are added, and ball milling is performed with aluminum oxide as a ball milling medium for 2 hours to obtain slurry B.
[0033] (3) Preparation of ceramics: The kaolin, talc and alumina are mixed in a ratio of kaolin: talc: alumina = 4:3:3 according to weight, 0.25% of methyl metal saponification liquid, 1% of methyl cellulose and 0.5% of polyether polyol are added, and the mixture is kneaded, mixed, aged at room temperature for 12 hours, refined and aged again at room temperature for 12 hours, and then sieved through a 250 mesh sieve three times to obtain a clay material with suitable properties. The clay material is put into an extruder to obtain a ceramic green body. Finally, the ceramic is calcined at a high temperature of 1350°C.
[0034] (4) Preparation of low-temperature coated catalyst: The above ceramic was immersed in slurry B for 5 minutes, 0.6% of the mass of slurry B in 8% aqueous solution of ammonium persulfate (ASP) was added as an initiator and 0.6% of tetramethylethylenediamine (TEMED) as a catalyst, and the ceramic was placed in an incubator at 60°C for gel curing for 5 hours, dried at 120°C for 2 hours, and calcined at 500°C to obtain a low-temperature coated catalyst.
[0035] Example 2
[0036] This embodiment provides a low-temperature coated catalyst, and the preparation method thereof specifically comprises the following steps:
[0037] (1) Pretreatment: The waste catalyst (TiO2, V2O5 and WO3 components in the waste catalyst still have utilization value) is screened and deashed, and then ground to a material particle size of 50 mesh to obtain a powder, and then the powder is mixed with soda ash in a mass ratio of 1 to 0.2, and the mixed material is roasted at a roasting temperature of 750°C. The roasted mixture is washed with three times the mass of water, sulfuric acid is added to make the solution pH value 3, and the solution is allowed to stand for 50 minutes to perform solid-liquid separation to obtain a slag, which is washed with a 1% dilute sulfuric acid solution. When the pH value of the washing solution is 3, the acid washing is stopped, and the slag is washed with pure water of the same mass as the slag, and then the slag is ball-milled to prepare a pre-slurry with a pre-slurry particle size of 800 mesh. The pre-slurry is mixed with metatitanic acid in a mass ratio of 1 to 0.1, and the mixed material is spray-dried at 350°C to form regenerated titanium dioxide after drying.
[0038] (2) Preparation of slurry B: Add regenerated titanium dioxide to a solution of ammonium metavanadate, ammonium metatungstate and oxalic acid, stir evenly, evaporate to dryness in a water bath at 80°C, and calcine at 500°C for 4 hours to obtain catalyst A. 20 parts by mass of a 20% silicon dioxide dispersion, 10 parts by mass of a 10% aluminum oxide hydrate dispersion, 25 parts by mass of acrylamide, 4.2 parts by mass of methylenebisacrylamide and 5 parts by mass of starch are mixed to obtain a premixed solution, silicon carbide powder with a particle size of 20 μm and graphite powder with a particle size of 5 μm are added to the premixed solution at a mass ratio of 15:1, and a 10% tetramethylammonium hydroxide (TMAH) aqueous solution with a powder mass fraction of 1.5% is added as a dispersant, SiC and graphite powder account for 48% of the total volume, 30 parts by mass of catalyst A are added, and ball milling is performed with aluminum oxide as a ball milling medium for 2 hours to obtain slurry B.
[0039] (3) Preparation of ceramics: Kaolin, talc and alumina are mixed in a ratio of kaolin: talc: alumina = 4:3:3 according to weight, 0.25% of methyl metal saponification liquid, 1% of methyl cellulose and 0.5% of polyether polyol are added, and the mixture is kneaded, mixed, aged at room temperature for 12 hours, refined and aged again at room temperature for 12 hours, and then sieved through a 250 mesh sieve three times to obtain a clay material with suitable properties. The clay material is put into an extruder to obtain a ceramic green body. Finally, the ceramic is calcined at a high temperature of 1350°C.
[0040] (4) Preparation of low-temperature coated catalyst: The above ceramic was immersed in slurry B for 5 minutes, 0.6% of the mass of slurry B in 8% aqueous solution of ammonium persulfate (ASP) was added as an initiator and 0.6% of tetramethylethylenediamine (TEMED) as a catalyst, and the ceramic was placed in an incubator at 60°C for gel curing for 5 hours, dried at 120°C for 2 hours, and calcined at 500°C to obtain a low-temperature coated catalyst.
[0041] Example 3
[0042] This embodiment provides a low-temperature coated catalyst, and the preparation method thereof specifically comprises the following steps:
[0043] (1) Pretreatment: The waste catalyst (TiO2, V2O5 and WO3 components in the waste catalyst still have utilization value) is sieved and deashed, and then ground to a material particle size of 30 mesh to obtain a powder, and then the powder is mixed with soda ash at a mass ratio of 1 to 0.2. The mixed material is roasted at a roasting temperature of 750°C, and the roasted mixture is washed with three times the mass of water to obtain a pre-chelate, and 8 parts of γ-polyglutamic acid are added to 120 parts of deionized water by mass, stirred evenly, and then dried at 120°C. After drying, the mixture is crushed and 10 parts of EDTMPA (ethylenediaminetetramethylphosphonic acid) are added at 40°C to obtain a glutamic acid chelating agent, and the pre-chelate and the glutamic acid chelating agent are mixed and stirred at a mass ratio of 1 to 0.2. Sulfuric acid was added to make the solution pH value 3, and the solution was allowed to stand for 50 minutes to perform solid-liquid separation to obtain slag, which was washed with a 1% dilute sulfuric acid solution. When the pH of the washing solution was 3, the acid washing was stopped, and the slag was washed with pure water of the same mass as the slag. The slag was then ball-milled to prepare a pre-slurry with a pre-slurry particle size of 900 mesh. The pre-slurry was mixed with titanic acid in a mass ratio of 1 to 0.1, and the mixed material was spray-dried at 350° C. to form regenerated titanium dioxide after drying.
[0044] (2) Preparation of slurry B: Add regenerated titanium dioxide to a solution of ammonium metavanadate, ammonium metatungstate and oxalic acid, stir evenly, evaporate to dryness in a water bath at 80°C, and calcine at 500°C for 4 hours to obtain catalyst A. 20 parts by mass of a 20% silicon dioxide dispersion, 10 parts by mass of a 10% aluminum oxide hydrate dispersion, 25 parts by mass of acrylamide, 4.2 parts by mass of methylenebisacrylamide and 5 parts by mass of starch are mixed to obtain a premixed solution, silicon carbide powder with a particle size of 20 μm and graphite powder with a particle size of 5 μm are added to the premixed solution at a mass ratio of 15:1, and a 10% tetramethylammonium hydroxide (TMAH) aqueous solution with a powder mass fraction of 1.5% is added as a dispersant, SiC and graphite powder account for 48% of the total volume, 30 parts by mass of catalyst A are added, and ball milling is performed with aluminum oxide as a ball milling medium for 2 hours to obtain slurry B.
[0045] (3) Preparation of ceramics: The kaolin, talc and alumina are mixed in a ratio of kaolin: talc: alumina = 4:3:3 according to weight, 0.25% of methyl metal saponification liquid, 1% of methyl cellulose and 0.5% of polyether polyol are added, and the mixture is kneaded, mixed, aged at room temperature for 12 hours, refined and aged again at room temperature for 12 hours, and then sieved through a 250 mesh sieve three times to obtain a clay material with suitable properties. The clay material is put into an extruder to obtain a ceramic green body. Finally, the ceramic is calcined at a high temperature of 1350°C.
[0046] (4) Preparation of low-temperature coated catalyst: The above ceramic was immersed in slurry B for 5 minutes, 0.6% of the mass of slurry B in 8% aqueous solution of ammonium persulfate (ASP) was added as an initiator and 0.6% of tetramethylethylenediamine (TEMED) as a catalyst, and the ceramic was placed in an incubator at 60°C for gel curing for 5 hours, dried at 120°C for 2 hours, and calcined at 500°C to obtain a low-temperature coated catalyst.
[0047] Comparative Example 1
[0048] The difference from Example 1 is that when preparing the low-temperature coating catalyst, 0.6% by mass of slurry B of 8% aqueous solution of ammonium persulfate (ASP) as initiator and 0.6% of tetramethylethylenediamine (TEMED) as catalyst are not added, and the gel is cured in an incubator at 60°C for 5 hours. The other contents are consistent with Example 1.
[0049] Comparative Example 2
[0050] The difference from Example 1 is that 0.25% of methyl metal saponified liquid and 0.5% of polyether polyol are added when preparing the ceramic, and 1% of methyl cellulose is missing. Other contents are consistent with Example 1.
[0051] Comparative Example 3
[0052] The difference from Example 1 is that when preparing slurry B, an equal mass portion of 10% hydrated aluminum oxide dispersion and an equal mass portion of starch are missing, and the other contents are consistent with Example 1.
[0053] Performance Testing
[0054] The examples and comparative examples were subjected to activity tests, water-sulfur poisoning tests and catalyst denitrification efficiency tests. Activity test: 2 mL of 20-40 mesh catalyst A particles were screened and placed in a reaction tube, with both sides fixed with asbestos. A mixed gas (space velocity 50000h-1) was introduced into the reaction tube. -1 , NO 1000ppm, O210%, NH31000ppm, N2 as carrier gas), heating from room temperature, 150~300℃ temperature range, keeping 50℃ for 20min each time, and testing tail gas concentration. Catalyst denitration performance evaluation see Figure 1 ; Water-sulfur poisoning test: 2 mL of 20-40 mesh catalyst A particles were selected and placed in a reaction tube, and both sides were fixed with asbestos. Mixed gas (space velocity 50000h-1) was introduced into the reaction tube. -1 , NO 1000ppm, O210%, NH31000ppm, SO2200ppm, water 10%, N2 as carrier gas), and react at 210℃ for 100h, and test the denitrification activity for 100h. Catalyst denitrification performance evaluation see Figure 2 .
[0055] Catalyst denitrification efficiency test: tested in a fixed bed reactor, the test conditions are: NO500ppm, NH3500ppm, O210%, SO230mg / Nm 3 , 5% H2O, N2 as balance gas, space velocity 2000h -1 , test temperature 150~300℃, catalyst 40×40 holes, length 500mm. Test results are as follows Figure 3 shown.
[0056] from Figure 3 It can be seen that the catalyst of the present invention has better activity at low temperature of 150-300°C.
[0057] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a low-temperature coated catalyst, characterized in that: The following steps are involved: Pretreatment steps: the waste catalyst is screened and deashed, then ground to obtain a grind, mixed with soda ash and calcined to obtain a mixture, washed and solid-liquid separated, washed with a dilute sulfuric acid solution, ball-milled to obtain a pre-slurry, and the pre-slurry is mixed with titanic acid and spray-dried to form regenerated titanium dioxide.
2. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: The spent catalyst contains TiO2, V2O5 and WO3.
3. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: In the pretreatment step, the waste catalyst is screened and deashed, and then ground to a material particle size of 30-50 mesh; the mass ratio of the ground material to soda ash is 1:0.2, and the roasting temperature is 750°C; three times the mass of pure water is used for washing; the pH value is adjusted to 3, and the solid-liquid separation is performed after standing for 50 minutes; a 1% dilute sulfuric acid solution is used for washing to a pH value of 3; the pre-slurry particle size is 800-1000 mesh; the pre-slurry is mixed with titanic acid in a mass ratio of 1:0.1 and spray-dried.
4. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: The method also includes the steps of preparing slurry B: adding regenerated titanium dioxide to a mixed solution containing an ammonium salt vanadium compound, an ammonium salt tungsten compound and a dicarboxylic acid, stirring in a water bath to evaporate to dryness, and calcining to obtain catalyst A; mixing silicon dioxide dispersion, hydrated aluminum oxide dispersion, acrylamide, methylenebisacrylamide and starch to obtain a premixed solution; adding silicon carbide powder and graphite powder; and adding a 10% aqueous solution of tetramethylammonium hydroxide; and adding catalyst A and ball milling and mixing for 2 hours to obtain slurry B.
5. The method for preparing a low-temperature coated catalyst according to claim 4, characterized in that: The ammonium salt vanadium compound is ammonium metavanadate, the ammonium salt tungsten compound is ammonium metatungstate, and the dicarboxylic acid is oxalic acid; after stirring, the mixture is evaporated to dryness in a water bath at 80° C.; and calcined at 500° C. for 4 hours to obtain catalyst A.
6. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: The method also includes the steps of preparing ceramics: mixing kaolin, talc and alumina, adding methyl metal saponification liquid, methyl cellulose and polyether polyol, kneading and mixing the clay, aging the clay once, refining and aging the clay twice, sieving the clay to obtain a clay material, putting the clay material into an extruder to obtain a ceramic green body, and calcining the clay to obtain the ceramic.
7. The method for preparing a low-temperature coated catalyst according to claim 6, characterized in that: The mass percentage concentration of the methyl metal saponification liquid is 0.25%, the mass percentage concentration of methyl cellulose is 1%, and the mass percentage concentration of polyether polyol is 0.5%; the first aging is a room temperature reaction for 12 hours; the second aging is a room temperature reaction for 16 hours; sieving through a 250 mesh sieve three times; and calcining at a high temperature of 1350°C to obtain ceramics.
8. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: The method also includes the steps of preparing a low-temperature coating catalyst: immersing the ceramic in slurry B, adding an 8% aqueous solution of ammonium persulfate and tetramethylethylenediamine, gelling and solidifying at 60°C, and heat-insulating, drying and calcining to obtain a low-temperature coating catalyst.
9. The method for preparing a low-temperature coated catalyst according to claim 8, characterized in that: Immerse the ceramic in slurry B for 5 minutes; add 0.6% of the mass of slurry B in an 8% aqueous solution of ammonium persulfate and 0.6% of tetramethylethylenediamine, place in an incubator at 60°C for gel curing for 5 hours, dry at 120°C for 6 hours, and calcine at 500°C to obtain a low-temperature coated catalyst.
10. The method for preparing a low-temperature coated catalyst according to claim 1, characterized in that: The pretreatment step also includes washing the calcined mixture with three times the mass of pure water to obtain a pre-chelate, adding 8 parts of γ-polyglutamic acid to 120 parts of deionized water by mass, stirring evenly and drying at 120° C., crushing after drying, adding 10 parts of EDTMPA at 40° C. to obtain a glutamate chelate, mixing the pre-chelate with the glutamate chelate at a mass ratio of 1 to 0.2, and performing solid-liquid separation.
Citation Information
Patent Citations
Supersize cordierite honeycomb ceramic carrier and production technique thereof
CN104387108A
Coated low-temperature flue gas denitration catalyst, and preparation method and application thereof
CN105126827A
Preparation method of vanadium-based oxide scr catalyst and catalyst prepared by using preparation method
CN109225203A
Method for preparing YAG-based core-shell structure rod-like transparent ceramic through gel casting
CN111253154A
Method for extracting tungsten trioxide from waste flue gas denitration catalyst by pyrogenic process
CN112390289A